Dragon Fruit Cultivation as a Solution to Rice Harvest Dependence in Kuwu Village, Madiun Regency - Abid Rohman; Thareq Kamal Taufik (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2021)
This article is the result of research that examines the efforts of the Kuwu village community to escape dependence on rice yields through dragon fruit cultivation by utilizing empty house yard assets with a Community Based Participatory Research (CBPR) approach. This approach provides an opportunity for researchers from the University of the UINSA KKN Team and the Kuwu village community to partner and collaborate to conduct research together to find solutions to problems faced by the community to improve their economic welfare. After conducting the inculturation stage with a Focus Group Discussion (FGD) with the Kuwu village community, and conducting an analysis of the initial assets owned by the local community, the researchers from the UINSA KKN Team group 18 together with the community focused on efforts to solve the problem of the dependence of the Kuwu village community on the results. rice harvesters by looking for additional income alternatives by cultivating dragon fruit by utilizing their empty home yard land. To solve this problem, researchers from the UINSA Team and residents of the Kuwu village community worked together in every stage of the research. There are four stages in the CBPR method, namely: (1) Foundation laying, (2) Research planning, (3) Data collection and analysis, (4) Determination of action on findings. Through these stages, it can be concluded that the results of this study include; first, the planting of dragon fruit seeds carried out by UINSA KKN students and residents of the Kuwu village community, starting with a literacy study and socialization about the benefits of dragon fruit initiated by local community leaders and extension workers from the local Agriculture Service; second, efforts to carry out various joint experiments to make food/snacks from processed dragon fruit carried out by PKK women and UINSA KKN students. This action was also followed up by the village government by initiating a working group (farmer's group) to oversee this program until finally realizing the aspirations of the community members to become a dragon fruit center village in the future.